Postmodern Morality in Adult Education: A Cross-Cultural Study - Donovan Plumb (Adult Education Research Conference, 2000)
Drawing on the recent work of Zygmunt Bauman, this paper explores the evolution of new moral sensibilities in postmodernity. It then reports on research that seeks to understand the meaning and implications of postmodern morality for adult educators in Nova Scotia, Canada and Kingston, Jamaica.